Global Governance of Global Monetary Relations: Rationale and Feasibility - Jeffry A. Frieden (Kiel Institute for the World Economy (IfW), 2008)
Is there a valid argument for international cooperation, and some form of international governance structure, in the international monetary realm? On the purely economic front, the argument is not strong. Yet a broader political economy approach concludes that national currency policy can in fact impose non-pecuniary externalities on partner nations. This is especially the case with major policy-driven misalignments, which cannot easily be countered by other governments. For example, one country's substantially depreciated currency can provoke powerful protectionist pressures in its trading partners, so that exchange rate policy spills over into trade policy in potentially damaging ways. Inasmuch as one government's policies create these sorts of costs for other countries, and for the world economy as a whole, there is a case for global governance. This might include some institutionalized mechanism to monitor and publicize substantial currency misalignments. While there appears to be little global political attention to such a mechanism now, there have been initiatives along these lines at the regional level, and there are some early stirrings of interest more generally.
Keywords: H87; F55; F42; 330; Exchange rates; macroeconomic policy coordination; Internationales Währungssystem; Internationale Währungspolitik; Global Governance; Welt